The Great East Japan Earthquake--Learning from Megadisasters : Knowledge Notes, Executive Summary - World Bank (Washington, DC, 2014)
The Great East Japan Earthquake (GEJE) was the first disaster ever recorded that included an earthquake, a tsunami, a nuclear power plant accident, a power supply failure, and a large-scale disruption of supply chains. On March 11, 2011 earthquake of magnitude 9.0 occurred in the Pacific Ocean off the coast of Japan's Tohoku region. The quake shook the ground as far away as western Japan and lasted for several minutes. A half hour later, a tsunami of unprecedented force broke over 650 kilometers of coastline, toppling sea walls and other defenses, flooding more than 500 km of land, and washing away entire towns and villages. This learning from Megadisasters, a knowledge sharing project is sponsored by the Government of Japan and the World Bank. The successes of Japan's Disaster Risk Management (DRM) system, as well as the ways in which that system could be improved, are reflected in the lessons drawn from the GEJE and presented in the initial reports from the Learning from megadisasters project: extreme disasters underscore the need for a holistic approach to DRM, preventive Investments pay, but be prepared for the unexpected, learning from disaster is key, as Japan has shown for the past 2,000 years, DRM is everyone's business, assessing risks and communicating them clearly and widely helps citizens make timely decisions to protect themselves, hazard maps can give the public a false sense of safety, if not properly communicated, Better management of information and communication is crucial in emergencies and recovery operations, coordination mechanisms must be developed and tested in normal times, so that they are ready for use in an emergency, and vulnerable groups must be protected and engaged.